Use of oXiris® hemoadsorption in sepsis and acute kidney injury: a retrospective cohort study in a resource-limited Colombian ICU - Ballesteros, David; Mantilla Villarreal, Andrea Cristina; Narváez Martínez, Sandra Cecilia; Saravia, Isabel; Martı́nez, Susan (Frontiers in Nephrology, 2025)
BackgroundSeptic shock with acute kidney injury (AKI) carries high mortality in resource-limited settings. The oXiris® membrane enables continuous renal replacement therapy (CRRT) with endotoxin and cytokine adsorption, but data from low- and middle-income countries are scarce.MethodsWe conducted a single-center retrospective cohort of adults with septic shock and KDIGO stage 2–3 AKI treated with CRRT using oXiris® in a Colombian public tertiary hospital (January 2021–March 2023). The primary outcome was renal recovery, defined as dialysis independence at discharge. Secondary outcomes included in-hospital mortality, vasopressor trajectories and hemodynamics over 72 hours, intensive care unit (ICU) length of stay, and outcomes stratified by COVID-19 status.ResultsFifty patients were analyzed (median age 56.5 [IQR 46.0–66.0] years; 32% male); 21 (42%) had confirmed SARS-CoV-2 infection. Norepinephrine requirements fell from 0.303 to 0.000 µg/kg/min over 72 hours (p<0.001), and vasopressin use declined to zero (p<0.001), while mean arterial pressure increased from 74.5 to 83.0 mmHg. In-hospital mortality was 62% (31/50) and was higher in patients with greater baseline severity (APACHE II 21.5 vs 14.5 in survivors; p=0.023). ICU length of stay was 14.0 days [5.0–22.5] and was longer in survivors than non-survivors (21.0 vs 8.0 days; p<0.001). Among survivors, 63% (12/19) were dialysis-independent at discharge. COVID-19 septic shock was associated with higher crude mortality (76% vs 52%) and lower renal recovery among survivors (9.5% vs 34%) compared with non-COVID sepsis.ConclusionsIn a resource-limited ICU, oXiris®-based CRRT was associated with rapid vasopressor de-escalation and clinically meaningful kidney recovery among survivors, but overall mortality remained high and severity-dependent. COVID-19 septic shock showed a distinct profile, with higher baseline severity, a trend toward higher mortality, and impaired renal recovery. These data support feasibility and safety of hemoadsorptive CRRT in constrained settings and justify prospective comparative evaluation.